Institutional entrepreneurs' social mobility in organizational fields - Waldron, Theodore L.; Fisher, Greg; Navis, Chad (Journal of Business Venturing, 2015)
This study examines how institutional entrepreneurs with marginalized social positions use institutional change to become more influential members of organizational fields. We analyze how the Rainforest Action Network (RAN) used rhetoric to garner more influence as it altered a key sourcing practice in the retail home-improvement field. Our findings indicate that RAN relied on three rhetorical practices, comprising an encompassing process, to cultivate positive associations between the new sourcing practices and its social position in the field. Overall, by specifying a marginalized entrepreneur's methods for leveraging one type of change to enact another, we enhance theory at the intersection of institutional entrepreneurship, institutional work, and rhetoric.